2014
DOI: 10.1002/anie.201405060
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ortho‐Hydroxylation–Defluorination of 2‐Fluorophenolates with a Bis(μ‐oxo)dicopper(III) Species

Abstract: The bis(μ-oxo)dicopper(III) species [Cu(III) 2 (μ-O)2 (m-XYL(MeAN) )](2+) (1) promotes the electrophilic ortho-hydroxylation-defluorination of 2-fluorophenolates to give the corresponding catechols, a reaction that is not accomplishable with a (η(2) :η(2) -O2 )dicopper(II) complex. Isotopic labeling studies show that the incoming oxygen atom originates from the bis(μ-oxo) unit. Ortho-hydroxylation-defluorination occurs selectively in intramolecular competition with other ortho-substituents such as chlorine or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 36 publications
3
44
0
2
Order By: Relevance
“…26 Using similar reaction conditions, we found that the S P MeAN oxidized 2,6-F 2 -phenolate to the corresponding 3-F-catechol in moderate yield (30%). Interestingly, coordination of the substrate to S P MeAN (Figure 4 bottom right, brown spectrum) was found to form a phenolate-bound O -type species [(MeAN) 2 Cu III 2 -(O 2− ) 2 (F 2 PhO − )] + ( O MeAN -F 2 PhO − , Figure 4, blue spectrum) with spectroscopic characteristics similar to other phenolate-coordinated O species.…”
Section: Resultsmentioning
confidence: 75%
“…26 Using similar reaction conditions, we found that the S P MeAN oxidized 2,6-F 2 -phenolate to the corresponding 3-F-catechol in moderate yield (30%). Interestingly, coordination of the substrate to S P MeAN (Figure 4 bottom right, brown spectrum) was found to form a phenolate-bound O -type species [(MeAN) 2 Cu III 2 -(O 2− ) 2 (F 2 PhO − )] + ( O MeAN -F 2 PhO − , Figure 4, blue spectrum) with spectroscopic characteristics similar to other phenolate-coordinated O species.…”
Section: Resultsmentioning
confidence: 75%
“…By contrast, the side-on peroxide of S P , while susceptible to protonation by acid [35,37,38], is capable of PPh 3 oxidation and can oxidize phenolates to catechols and catechols to quinones through an electrophilic mechanism [34,37]. The O species are the most potent oxidants, capable of phenolate hydroxylation, C-F activation, and C-H activation [2,18,25,3941]. The extremely compact nature of the T species precludes most reactivity, with the exceptions of proton-coupled electron transfer (PCET) from weak O-H substrates and oxidation of PPh 3 [23,42–44].…”
Section: General Reactivitymentioning
confidence: 99%
“…A recent example of a C−F hydroxylation reaction mediated by a high-valent copper species is also promoted by a sacrificial reductant. 100 …”
mentioning
confidence: 99%